Pendidikan Karakter Berbasis Humanis Mahasiswa STAB Maitreyawira Pekanbaru - Sonika Sonika; Yadi Sutikno; Rida Jelita; Hosan Hosan; Irawati Irawati (STAB Maitreyawira, 2020)
This research focused on the humanistic character education of college students in STAB Maitreyawira. It is to analyze the character education implementation and college students’ humanist behavior. By using a case study in qualitative research design, the sample is a purposive sample of college students in STAB Maitreyawira. Data collection by questionnaire in google form, a document study, interview, and triangulation. Data analysis with an interactive model. This research revealed that: 1) The document study indicates that the academy has regulated and implemented the culture such as trustworthy, well-mannered, responsive, creative, and three-harmony (harmonious joy, harmonious getting-along, and harmonious togetherness). The character education implementation is considered as good and well-improved with the indicator created by the lecturers and students with supportive theory. 2) Some improvements in students’ behavior and attitude in terms of the three-harmony (harmonious joy, harmonious getting-along, and harmonious togetherness) from the aspects of knowledge, behavior, and experience. 3) The most dominant aspect from the three-harmony is regarding harmonious joy while the other two are described with Mentimeter. In conclusion, the college students of STAB Maitreyawira are, conceptually, able to explain in terms of cognitive, affective, and psychomotor with a test score above 85%. They also uphold, respect, and glorify life in the three-harmony aspects so that it can create a positive atmosphere full of optimist, non-violence, and friendliness among the school residents. The academy’s culture prioritizes humanistic moral value with the spirit of the Universal Family as the outcome of the graduates of STAB Maitreyawira.